LOCAL GOVERNMENT POSITION IN EQUITY PARTICIPATION TO BUMD, BUMN AND THIRD PARTIES - Nurasiah Harahap (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
The state in carrying out government administration activities is carried out through government institutions or is usually categorized as a public legal entity. Based on the statutory regulations, it is stated that any capital participation or additional capital participation to regional companies must be regulated in a separate regional regulation regarding participation or additional capital. Regional Government equity participation can be implemented if the amount to be included in the relevant budget year has been stipulated in a Regional Regulation. In Article 1654 of the Civil Code which reads "All legally established legal entities, as well as private persons, have the power to carry out civil acts, without prejudice to laws that change that power, limit it or subject it to certain procedures. The position of the government as a legal entity is not strictly regulated in the Civil Code. Knowledge about the Government as a legal entity is only obtained from secondary legal materials that explain the Civil Code. Regional Governments can carry out equity participation in state-owned enterprises and/or can be transferred to state-owned enterprises (BUMD). Equity participation is carried out in accordance with the provisions of laws and regulations. Regional capital participation is determined by regional regulation.